Pharmacokinetics of Amlodipine Besylate at Delivery and During Lactation. Issue 3 (September 2019) - Morgan, J.L.; Kogutt, B.K.; Meek, C.; Stehel, E.K.; McIntire, D.D.; Sheffield, J.S.; Roberts, S.W.
Abstract : ( Pregnancy Hypertens . 2018;11:77–80. Doi:10.1016/j.preghy.2018.01.002) The management of chronic hypertension, which affects ~5% of all US pregnancies, requires careful balance. While many drugs used to treat hypertension have been well-studied, there is a lack of options that have been adequately studied during pregnancy and lactation. Amlodipine is an ideal option for use in pregnancy due to its long half-life, infrequent dosing, low cost and positive side-effect profile, but more data are needed on its use in pregnant and lactating patients and whether it crosses the placenta. This study aimed to evaluate the pharmacokinetics of amlodipine besylate in a population of pregnant women during delivery and postpartum lactation.